Endocrine Cephalic Phase Responses to Food Cues: A Systematic Review - Lasschuijt, Marlou P (Adv Nutr, 2020)
Cephalic phase responses (CPRs) are conditioned anticipatory physiological responses to food cues. They occur before nutrient absorption and are hypothesized to be important for satiation and glucose homeostasis. Cephalic phase insulin responses (CPIRs) and pancreatic polypeptide responses (CPPPRs) are found consistently in animals, but human literature is inconclusive. We performed a systematic review of human studies to determine the magnitude and onset time of these CPRs. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to develop a search strategy. The terms included in the search strategy were cephalic or hormone response or endocrine response combined with insulin and pancreatic polypeptide (PP). The following databases were searched: Scopus (Elsevier), Science Direct, PubMed, Google Scholar, and The Cochrane Library. Initially, 582 original research articles were found, 50 were included for analysis. An insulin increase (≥1μIU/mL) was observed in 41% of the treatments (total n = 119). In 22% of all treatments the increase was significant from baseline. The median (IQR) insulin increase was 2.5 (1.6–4.5) μIU/mL, 30% above baseline at 5± 3 min  after food cue onset (based on study treatments that induced ≥1 μIU/mL insulin increase). A PP increase (>10 pg/mL) was found in 48% of the treatments (total n = 42). In 21% of the treatments, the increase was significant from baseline. The median (IQR) PP increase was 99 (26–156) pg/mL, 68% above baseline at 9± 4 min  after food cue onset (based on study treatments that induced ≥1 μIU/mL insulin increase). In conclusion, CPIRs are small compared with spontaneous fluctuations. Although CPPPRs are of a larger magnitude, both show substantial variation in magnitude and onset time. We found little evidence for CPIR or CPPPR affecting functional outcomes, that is, satiation and glucose homeostasis. Therefore, CPRs do not seem to be biologically meaningful in daily life.